Pengaruh Penggunaan Media Padlet Terhadap Hasil Belajar Warga Belajar Paket B pada Mata Pelajaran Bahasa Indonesia di PKBM Suka Maju Sejahtera Kota Padang - Shofy, Rachma; Aini, Wirdatul (Universitas Negeri Padang, 2024)
The investigation began with the academic performance of individuals taking the Indonesian Language Package B course at PKBM Suka Maju Sejahtera Padang City which was below standard. The educational tools used by teaching staff are thought to be less attractive for students enrolled in Package B. The aims of this research are: (1) to determine the characteristics of Indonesian language educational tools which include Padlet for Package B, (2) to evaluate the impact of Padlet educational tools on academic achievement and (3) evaluating the impact of using Padlet on the academic results of PKBM Suka Maju Sejahtera Package B participants in Padang City. This research uses a quasi-experimental design and uses quantitative methods to find out whether the Padlet tool affects academic performance in the Indonesian language course for Package B residents at PKBM Suka Maju Sejahtera, Padang City. The aim of this research is the sample population, namely students studying package B class IX at PKBM Suka Maju Sejahtera, totaling 30 students. This research uses One Group Posttest True Experiment Design. The validity test of the test instrument was given to SIMA Mata Air High School students and 17 objective questions were obtained, to be tested as pre-test and post-test questions on Package B teaching residents at PKBM Suka Maju Sejahtera. The results of the research show that: (1) The application of the Padlet tool in the Package B Indonesian language course at PKBM Suka Maju Sejahtera is effective in improving student educational achievement. (2) Documentation of high academic results is proven through students' understanding and involvement in the content provided by the teacher. (3) There is a significant influence of the use of Padlet educational tools on individual academic achievement in Package B at PKBM Suka Maju Sejahtera Padang City as seen from the results of the T test analyzed using SPSS version 0.16, where the calculated r (0.390) exceeds the r table (0.361), and in the Correlation Test, t count (1.300) is below t table (2.050) at the significance level of 0.05 for n: 30.